Identifikasi Risiko Kecelakaan Kerja pada Proyek Pembangunan Gedung Rumah Sakit Siti Khodijah Sidoarjo - Aminestia, Tharisa Destin (Universitas Negeri Surabaya, 2023)
ABSTRACT The development of construction projects generally contains activities that are very risky and have the potential for unwanted events to occur. The risks that may occur on the project vary greatly due to the factors of the workers themselves and from the project environment, from these risks it is possible that construction work is one of the supporters of a fairly high number of work accidents. Therefore, a way or effort is needed by identifying a risk in work accidents that may occur from each job on the Siti Khodijah Sidoarjo Hospital Building construction project to minimize the number of work accidents on the project. This research uses descriptive qualitative methods that aim to explain a problem formulation and describe solutions in depth and detail. Descriptive qualitative method is by conducting direct observations in the project environment, interviews with safety officers or K3, and literature studies to identify risks that may occur in the Siti Khodijah Sidoarjo Hospital Building Construction Project. The results of this study obtained 34 risks of work accidents which were reviewed from four variables, namely materials, tools, workers or humans, and the environment. The risks of work accidents were obtained from interviews, observations, and literature studies. The results of the 34 risks of work accidents based on the variables found there are 11 risks from the material variable, 9 risks from the tool variable, 9 risks from the worker or human variable, and 5 risks from the environmental variable.